HUBUNGAN KECEPATAN REAKSI PUKULAN FOREHAND PERMAINAN TENIS MEJA SISWA SMP NEGERI 11 KONAWE SELATAN - Desi Ratnasari; Muhammad Rusli; Suhartiwi (Universitas Halu Oleo, 2021)
This research is mean in descriotive correlational research. The purpose of this study was to determine whether there is a correlational between arm muscle hand reaction speed and forehand ability in the table tennis game of SMP Negeri 11 Konawe Selatan students. This rype of descriptive research using the correlational method. The populasi in this study were all students of SMP Negeri 11 konawe selatan totaling 272. The sampling technique was carried out using purposive sampling technique, which is based on predetermined criteria, namely as many as 41 students. The instrument used to measure the speed of the reaction was the Nelson speed of movement test, while the instrument used to measure the ability of the forehand hit was the mott lockhart table tennis test or the back board test. Hand reaction speed data is taken through the Nelson speed of movement test while the forehand stroke ability data is taken through the mott lockhart table tennis test or back board test. The analysis technique used to analyze the proposed hypothesis is the correlation test using SPSS version 26. The results obtained from testing the hypothesis of hand reaction speed with the ability of forehand strokes in table tennis, where the correlation value (rxy) = -0.302 with a significant value = 0.055˃0.05. From the results obtained, it can be concluded that there is an insignificant counterclockwise relationship between hand reaction speed and the ability of forehand strokes in the table tennis game of SMP Negeri 11 Konawe Selatan students